Effect of cobalt doping on the device properties of Sb2S3-sensitized TiO2 solar cells. (1st May 2019) - Cerdán-Pasarán, Andrea; López-Luke, Tzarara; Mathew, X.; Mathews, N.R.
Graphical abstract: Highlights: Cobalt doped Sb2 S3 -sensitized TiO2 solar cells by solution processing technique. Better conductivity and charge transport by doping enhanced photovoltaic properties. Above 2 mol % of cobalt doping there was a decrease photovoltaic performance. Abstract: In this work, we studied the photovoltaic performance of cobalt-doped Sb2 S3 sensitized TiO2 solar cells. The effect of cobalt concentration on structural, optical and photovoltaic properties of the solar cells was analyzed. The X-ray diffraction pattern of the Sb2 S3 and Sb2 S3 :Co samples matched well with the stibnite phase, and showed an increment in the crystal size from 25 nm to 31 nm with the cobalt doping. The photoelectrodes have a direct band gap in the range of 1.6–1.67 eV. The dark conductivity of the TiO2 layer was increased by two orders of magnitude by sensitizing with Sb2 S3 which was further increased by one order after Co doping. Likewise, a betterment of photosensitivity was also seen with Sb2 S3 :Co. The power conversion efficiency of the sensitized solar cells improved from 0.52% for Sb2 S3 to 1.33% for Sb2 S3 :Co samples using 2 mol% of cobalt. This enhancement was related to the charge transport, verified from the impedance characterization, where a decrease in charge transport resistance was observed for Sb2 S3 :Co sensitized solar cells.